Gradient concentration strip–specific epidemiological cut-off values of antifungal drugs in various yeast species and five prevalent Aspergillus species complexes. (May 2023) - Mercier, Victor; Letscher-Bru, Valérie; Bougnoux, Marie-Elisabeth; Delhaes, Laurence; Botterel, Francoise; Maubon, Danièle; Dalle, Frédéric; Alanio, Alexandre; Houzé, Sandrine; Dannaoui, Eric; Cassagne, Carole; Cassaing, Sophie; et al.
Abstract: Objectives: To determine the epidemiological cut-off values (ECVs) of ten antifungal agents in a wide range of yeasts and Aspergillus spp. using gradient concentration strips. Methods: The minimum inhibitory concentrations for amphotericin B, anidulafungin, caspofungin, micafungin, flucytosine, fluconazole, itraconazole, isavuconazole, posaconazole, and voriconazole, determined with gradient concentration strips at 35 French microbiology laboratories between 2002 and 2020, were retrospectively collected. Then, the ECVs were calculated using the iterative method and a cut-off value of 97.5%. Results: Minimum inhibitory concentrations were available for 17 653 clinical isolates. In total, 48 ECVs (including 32 new ECVs) were determined: 29 ECVs for frequent yeast species (e.g. Candida albicans and itraconazole/flucytosine, and Candida glabrata species complex [SC] and flucytosine) and rare yeast species (e.g. Candida dubliniensis, Candida inconspicua, Saccharomyces cerevisiae, and Cryptococcus neoformans ) and 19 ECVs for Aspergillus flavus SC, Aspergillus fumigatus SC, Aspergillus nidulans SC, Aspergillus niger SC, and Aspergillus terreus SC. Conclusions: These ECVs can be added to the already available gradient concentration strip–specific ECVs to facilitate minimum inhibitory concentration interpretation and streamline the identification of nonwild type isolates.